2011
DOI: 10.1002/jbmr.338
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral accrual in 4- to 10-year-old precompetitive, recreational gymnasts: A 4-year longitudinal study

Abstract: Competitive female gymnasts have greater bone mineral measures than nongymnasts. However, less is known about the effect of recreational and/or precompetitive gymnastics participation on bone development. The purpose of this study was to investigate whether the differences previously reported in the skeleton of competitive female gymnasts are also demonstrated in young children with a current or past participation history in recreational or precompetitive gymnastics. One hundred and sixty-three children (30 gy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
24
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 24 publications
8
24
0
Order By: Relevance
“…Details of the YRGS have been published elsewhere [11]. In brief, 178 participants (4-6 years of age) were recruited between 2006 and 2009 into a mixed longitudinal study examining the influence of early life exposure to recreational gymnastics participation on bone development.…”
Section: Participantsmentioning
confidence: 99%
See 3 more Smart Citations
“…Details of the YRGS have been published elsewhere [11]. In brief, 178 participants (4-6 years of age) were recruited between 2006 and 2009 into a mixed longitudinal study examining the influence of early life exposure to recreational gymnastics participation on bone development.…”
Section: Participantsmentioning
confidence: 99%
“…Details of the NPAQ as used in this cohort have been described in detail elsewhere [11]. In brief, the NPAQ ranks individuals based on parental reports of their child's current activity preferences and everyday activity choices [24].…”
Section: Physical Activity Assessmentsmentioning
confidence: 99%
See 2 more Smart Citations
“…(5,6) It has also been found that sports training during childhood and adolescence increases bone mineral content and density. (7,8) However, it is unclear if the benefits are maintained after retirement from sport and removal of the osteogenic stimulus. Currently, the best evidence linking childhood exercise to bone health in adulthood arises from cross-sectional and short-term prospective studies in retired competitive athletes.…”
Section: Introductionmentioning
confidence: 99%